Estimating Interspecific Economic Risk of Bird Strikes With Aircraft - DeVault, Travis L.; Blackwell, Bradley F.; Seamans, Thomas W.; Begier, Michael J.; Kougher, Jason D.; Washburn, Jenny E.; Miller, Phyllis R.; Dolbeer, Richard A. (DigitalCommons@University of Nebraska - Lincoln, 2018)
The International Civil Aviation Organization promotes prioritization of wildlife management on airports, among other safety issues, by emphasizing the risk of wildlife–aircraft collisions (strikes). In its basic form, strike risk comprises a frequency component (i.e., how often strikes occur) and a severity component reflecting the cost of the incident. However, there is no widely accepted formula for estimating strike risk. Our goal was to develop a probabilistic risk metric that is adaptable for airports to use. Our specific objectives were to 1) update species-specific, relative hazard scores (i.e., the likelihood of aircraft damage or effect on flight when strikes occur) using recent U.S. Federal Aviation Administration (FAA) wildlife strike data (2010–2015); 2) develop 4 a priori risk models, reflecting species-specific strike data and updated relative hazard scores; 3) test these models against independent data (monetary costs associated with strikes); and 4) apply our best model to strike data from 4 large, FAA-certificated airports to illustrate its application at the local level. Our best-fitting risk model included an independent variable that was an interaction of quadratic transformed relative hazard score and number of wildlife strikes (r2=0.74). Top species in terms of estimated risk nationally were red-tailed hawk (Buteo jamaicensis), Canada goose (Branta canadensis), turkey vulture (Cathartes aura), rock pigeon (Columba livia), and mourning dove (Zenaida macroura). We found substantial overlap among the top 5 riskiest species locally across 3 of 4 airports considered, illustrating the degree of site specific differences that affect risk. Strike risk is dynamic; therefore, future work on risk estimation should allow for model adjustment to reflect ongoing wildlife management actions at airports that could influence future strike risk. Published 2018. This article is a U.S. Government work and is in the public domain in the USA.